Analysis of the Law Concerning Horse, Mule and Donkey Meat From the Quranic Prism - Niyazov, Ahmed; Ağamoğlanov, Hilal (Scholarya Demo Journal of Ruby, 2021)
The names of animals that are halal in Islamic law, such as sheep, goats, camels and cows, are mentioned in the Holy Qur'an. Moreover, the Islamic law also mentions a horse, mule and donkey, which differ in law regarding the edibility of their meat. Some claim that the reason for consuming the meat of these animals is obvious from verses 5-8 of the Holy Qur'an's sura “anNakhl”. However, there is evidence that the verger is giving this statement, both in hadith and in historical events on this occasion. The article notes the Ijtihad and the arguments of the Shiite and Sunni Faqihs on this subject, as well as the relevant opinions of scholars. The conclusion is that verse 8 of the al-Nakhl sura in the Holy Qur'an is not considered an evidence of a ban on the consumption of horse, mule and donkey meat. Since, these ayats were sent to Mecca before Hijra, and the announcement of donkey meat and mule by haram took place at the Battle of Khaibar 7 years after Hijra. In addition, the above-mentioned animals are not najis in essence like pigs, and therefore their haram can be caused by certain reasons. During the Battle of Khaibar, such a reason could be that one of these animals a donkey, was used to carry goods, and could also be a “jellale” (trained to eat human feces).